MANAJEMEN PERUBAHAN KURIKULUM KTSP 2006 KE-KURIKULUM 2013 DI SMA NEGERI 1 KEDIRI - Bashori Bashori (Jurnal Penelitian LPPM (Lembaga Penelitian dan Pengabdian kepada Masyarakat) IKIP PGRI MADIUN, 2016)
This study aims to know (1) the implementation of management of change the curriculum KTSP 2006 to the curriculum 2013, (2) to know the impact of the implementation of management of change toward the learning process and (3) to know the supporting and resistance factor of the implementation of the management of change by SMAN 1 Kediri. This research is a field research (qualitative). The subject of study uses the purposive & snowball sampling. The process of collecting data uses interview, observation, and documentation. The technique of analyzing data uses data analysis techniques with a qualitative descriptive- inductive approach. The results of this research are The First, the implementation process of curriculum KTSP to the curriculum 2013 in SMAN 1 Kediri consist of activities: Planning, Organizing, Actuating, and Controlling. Practically, all of these functions is work effectively, only the controlling process that has not been able to run effectively and tangible in the field. The second, the impact of the management of changes to the learning process, namely: Guidance and Counseling (BK), labeling majors (specializations), teacher book and student book, the concept of subjects, the concept of assessment, and scientific approach (scientific approach). The third, the supporting & resistance factors of the implementation of curriculum 2013 in SMAN 1 Kediri namely, as supporting factors include the former of RSBI schools, the former of Full Day School, Learners, teacher, and analysis of the curriculum. As the resistance factors are Procurement of books, Facilities and infrastructure, and funding.